Die funksie van die politieke party in die burgerstaat ('n staatsfilosofiese studie) - Van Rooyen, Jacobus Cornelius (University of the Free State, 1970)
Abstract not available
Keywords: Dissertation (M.A. (Political Science))--University of the Free State, 1970; Political parties; South Africa -- Politics and government; Democracy -- South Africa -- Evaluation